Rwanda : 2006 Article IV Consultation, First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Request for Waiver of Nonobservance of Performance Criteria. (IMF Staff Country Reports; Country Report, 2007)
The 2006 Article IV Consultation on Rwanda highlights medium-term stimulating growth to reduce poverty. The government of Rwanda's medium-term policies address the country's challenges to increase growth and make headway toward the Millennium Development Goals. Executive Directors commended Rwanda's sound macroeconomic management and progress on structural reforms and social reconstruction. Together with debt relief, this has led to macroeconomic stability, strong economic growth, and progress in advancing toward the Millennium Development Goals. Directors emphasized the need for increased training to build expertise and overcome capacity constraints in the public sector.